Methodological approaches to determining the system of indicators for monitoring the socio-economic development of the region - Shelomentseva В.П.; Bespalyy С.В.; Ifutina Е.А. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
An important problem that should be solved by the public authorities responsible for regional governance is the development of a system for effective monitoring of the socio-economic development of the region. A reason for this is the lack of information on the status and dynamics of the main indicators affecting the processes in the regions. The article examines studies carried out in different countries devoted to the analysis and assessment of the level of socio-economic development of the territory at the regional level. The article discusses various aspects of research on assessing the development of regions: a system of indicators, possible sources of information, processing methods and the form of the result. In many countries there is still a lack of reliable data on changes in socio-economic processes at the regional level, the authors summarized the experience of various studies in the article and proposed the author’s vision of the system of socio-economic indicators of regions. Based on the analysis of various planning and monitoring methods for the socio-economic development of regions, the article proposes a system for monitoring the socio-economic development of a region, which provides for an assessment of the development of a territory by seven groups of indicators. To analyze the available research in the field of assessing the socio-economic development of regions, there have been used methods of comparative analysis and generalization, statistical analysis.